Rice straw biochar mitigates metal stress in corn and assists in the phytoattenuation of a slag-contaminated soil - Venâncio de Lima Veloso; Fernando Bruno Vieira da Silva; Paula Renata Muniz Araújo; Taciana da Silva Paraizo; Edivan Rodrigues de Souza; Clístenes Williams Araújo do Nascimento (Revista Brasileira de Ciência do Solo)
ABSTRACT Soils polluted by potentially toxic elements (PTEs) pose a high risk to human health and must be remediated. Applying biochar to such soils can reduce metal bioavailability and phytotoxicity, improving phytoremediation techniques. This study aimed to assess the effects of rice straw biochar (RSB) on mitigating metal stress and accumulation of Si, Cd, Pb, and Zn in corn plants grown in soil contaminated by metallurgy slag. Soil in pots was amended with RSB rates equivalent to 0, 5, 10, 20, and 30 Mg ha-1 and grown with corn for 45 days. Chlorophyll fluorescence, photosynthetic pigment contents, and gas exchange parameters were evaluated as PTEs toxicity indicators. The RSB rates significantly increased Si uptake while reducing Cd, Pb, and Zn accumulation in corn shoots. The addition of 30 Mg ha-1 RSB promoted 18, 34, and 37 % reductions for Zn, Cd, and Pb in the plants, respectively. Photosynthetic rate, transpiration, and stomatal conductance increased by 68, 67, and 55 %, while chlorophyll a, b, and carotenoid contents increased by 77, 57, and 42 %, correspondingly. Chlorophyll fluorescence measurements showed a linear and positive relationship between photosystem II energy consumption efficiency (Fv/Fm) and RSB rates. The combined use of RSB and corn can effectively phytoattenuate Cd, Pb, and Zn contamination by enhancing biomass and improving maize tolerance to PTE stress. This sustainable and cost-effective strategy offers environmental and health benefits while generating income for stakeholders in resource-limited areas.